The Urgency of Strengthening Judges’ Authority in the Rechtvinding Process - Eko Budi Susilo; Tri Susilowati; Naya Amin Zaini (Dinasti Research, 2024)
The rechtvinding process, or legal discovery, is one of the essential functions performed by judges, particularly when dealing with cases that are not clearly regulated in the laws and regulations. The urgency of strengthening judges' authority in the rechtvinding process is crucial considering the limitations of positive law that often cannot keep pace with the increasingly complex dynamics of society. On the one hand, this authority enables judges to ensure justice and meet the legal needs of the community. However, on the other hand, challenges such as ambiguities in regulations, subjectivity in interpretations, and a lack of accountability can reduce legal certainty. This article aims to examine the urgency of strengthening regulations regarding judges' authority in the rechtvinding process and to identify the weaknesses present in this process. Additionally, this article offers various measures that can be taken to enhance legal certainty, such as developing consistent jurisprudence and implementing stronger accountability principles. Thus, it is hoped that strengthening judges' authority in the rechtvinding process can support the achievement of a more responsive, fair, and trustworthy legal system for society.